Variabilitas Genetik 11 Klon Kakao Lokal dari Sumatera Barat Berdasarkan Marka SSR - Cici Tresniawati; Nur Kholilatul Izzah; Indah Sulistiyorini; Ilham Nur Ardhi Wicaksono (Pusat Penelitian dan Pengembangan Perkebunan, 2017)
Indonesia is the third largest cacao producing-country in the world and known having many superior local clones, such as that found in Lima Puluh Kota Regency, West Sumatra. However, there is lack of information about genetic background of those local cacao clones. This study aimed to assess genetic variability of 11 local cacao clones collected from Lima Puluh Kota Regency, West Sumatra using SSR markers. The research was conducted in the Integrated Laboratory, Indonesian Industrial and Beverage Crops Research Institute (IIBCRI), Sukabumi, from August to November 2016. The genetic variabilities of local cacao studied were compared with 9 national varieties as reference genomes. Total genomic DNA of the plants was isolated using CTAB method. Cacao DNA was amplified using 18 SSR markers to determine their genetic variability. Afterward, the amplified DNA was separated using 6% non-denaturing polyacrylamide gel electrophoresis. The result exhibited that 12 markers were polymorphic. Further analysis of these polymorphic markers using PowerMarker program revealed a total of 83 alleles were obtained from all cacao clones analyzed. Meanwhile, PIC values ranged from 0.55 to 0.86 with an average of 0.70. A genetic similarity matrix based on UPGMA revealed three main groups at 68% similarity coefficients. Interestingly, all of the 11 local cacao clones were clearly distinguished each other and also from the national varieties. The result demonstrated the usefulness of SSR markers for discriminating local cacao clones. Further study is required to use these local clones in cacao breeding programs.